Improving mathematics learning outcomes on fraction material using pbl-based petis (automatic fraction) media for elementary school students - Icha Biassari; Novita Agung Wicaksono; Hari Sunaryo (Universitas Nusantara PGRI Kediri, 2024)
This research aims to improve mathematics learning outcomes, especiallyfraction material, in grade 4 students at SDN 2 Banaran by using PETIS (AutomaticFractions) media based on problem based learning. This research has three cycles, eachcycle consisting of four stages, namely planning, action, observation and reflection inaccordance with the classroom action research model of Stephen Kemmis and RobynMcTaggarat. The data collection techniques used are document studies, questionnaires,interviews, observations and tests. Meanwhile, the data analysis techniques used are datareduction, data exposure, and data conclusion. An important finding in this classroomaction research is that there was an increase in the percentage of classical completenessand the average class score in each cycle which ultimately reached the indicator ofresearch success. Details of this increase include cognitive diagnostic assessmentactivities, student learning outcomes have a classical completion percentage of 36.84%which is classified as poor with an average class score of 59.47. In the first cycle, studentlearning outcomes had a classical completion percentage of 47.36% which was classifiedas sufficient with an average class score of 67.36. In cycle II, student learning outcomeshad a classical completion percentage of 63.15%, which was classified as good, with anaverage class score of 77.89. In cycle III, student learning outcomes had a classicalcompletion percentage of 84.21% which was classified as very good with an average classscore of 84.21.